1985
DOI: 10.1002/pol.1985.170230805
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Ziegler–Natta catalysis. II. Ethylene polymerization by IVB transition metal complexes/methyl aluminoxane catalyst systems

Abstract: Homogeneous Ziegler‐Natta systems for the ethylene polymerization, deriving from R2R2′M complexes (R = cyclopentadienyl; R′ = alkyl, aryl; M = Ti, Zr, Hf) and oligomeric oxoalane compounds, were studied. Further results concerning the methyl aluminoxane synthesis and the related chemistry are reported. On the basis of spectroscopic data a delocalized electronic structure could be inferred for these compounds. Results from polymerization experiments showed that the highest productivities are obtained only by ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
2

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(92 citation statements)
references
References 38 publications
2
88
2
Order By: Relevance
“…27 Al-NMR investigations show that the in situ hydrolyzed products of TMA with H 2 O are tetra-coordinated, and their molecular weights are low. High polymerization activity could also be achieved with MAO with low molecular weight as the cocatalyst, which is different from the result reported by Giannetti et al 3 5. Cp 2 ZrCl 2 can be partially monoalkylated by TMA, MAO, and the in situ partially hydrolyzed products of TMA with water.…”
Section: Resultscontrasting
confidence: 79%
See 2 more Smart Citations
“…27 Al-NMR investigations show that the in situ hydrolyzed products of TMA with H 2 O are tetra-coordinated, and their molecular weights are low. High polymerization activity could also be achieved with MAO with low molecular weight as the cocatalyst, which is different from the result reported by Giannetti et al 3 5. Cp 2 ZrCl 2 can be partially monoalkylated by TMA, MAO, and the in situ partially hydrolyzed products of TMA with water.…”
Section: Resultscontrasting
confidence: 79%
“…It may be concluded that at relatively lower concentration, the spectrum mainly displays the resonance of the residual TMA and MAO with low molecular weight (2), and at higher concentration it displays that of MAO with relatively high molecular weight (3). It can also be concluded that the hydrolysis concentration of TMA is important for the molecular weight of MAO after the same reaction time.…”
Section: Influence Of the Hydrolysis Concentration Of Tmamentioning
confidence: 89%
See 1 more Smart Citation
“…The UV region of the coated samples presents several absorption bands assigned to the solvent (toluene) and a broad, less intense, band around 300 nm due to an oxygen to aluminum p π -d π dative bond, typical for the oxygen-bridged organoaluminum compounds. 17,18 In the near-IR region (see the insert, Figure 3), the samples are characterized by several absorption bands: the band at 1410 nm could be assigned to the overtone of the stretching mode of the silanol groups, while the band at 1458 nm could be assigned to the overtone of the OH stretching in water molecules. Both of them are decreasing during triisobutylaluminum hydrolysis.…”
Section: Preparation Of the Keggin Ion Solutions And [Almentioning
confidence: 99%
“…6 Reddy et al 7 reported that addition of TMA to the Cp 2 ZrCl 2 -MAO system for ethylene polymerization leads to a dramatic increase in catalyst productivity and catalyst lifetime. However, as reported by Giannetti et al 8 and Chien and Wang, 9 catalytic activities decrease with increasing an [TMA]/[MAO] ratio when Cp 2 Zr(CH 2 C 6 H 5 ) 2 and (Ind) 2 ZrMe 2 , and Cp 2 ZrCl 2 were used in ethylene polymerizations.…”
Section: Introductionmentioning
confidence: 58%